2023
DOI: 10.3390/jrfm16120505
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Determinants of FinTech Adoption: Integrating UTAUT2 with Trust Theoretic Model

Muhammed Basid Amnas,
Murugesan Selvam,
Mariappan Raja
et al.

Abstract: Financial technology (FinTech) is transforming the financial services industry by offering innovative, convenient solutions for businesses and individuals. This study examines the factors influencing FinTech adoption, with a special focus on trust. By integrating insights from both the unified theory of acceptance and use of technology (UTAUT2), and the trust theoretic model (TTM), this research uncovers critical determinants of FinTech adoption. Utilizing survey responses obtained from 399 participants, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…First, the results demonstrated that trust significantly and positively influenced the use of FinTech services (Hypothesis 1), concurring with prior research (Alrawad et al 2023;Amnas et al 2023;Savitha et al 2022;Wang et al 2019;Zarifis and Cheng 2022). This confirmation established the essential function that trust plays in promoting the utilization of FinTech platforms.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…First, the results demonstrated that trust significantly and positively influenced the use of FinTech services (Hypothesis 1), concurring with prior research (Alrawad et al 2023;Amnas et al 2023;Savitha et al 2022;Wang et al 2019;Zarifis and Cheng 2022). This confirmation established the essential function that trust plays in promoting the utilization of FinTech platforms.…”
Section: Discussionsupporting
confidence: 86%
“…Among the primary determinants of users' attitudes and behaviors toward FinTech services, trust stands out as a fundamental factor (Zarifis and Cheng 2022). It contributes to user confidence, increases user loyalty, diminishes perceived risk, and promotes positive word-of-mouth (Amnas et al 2023;Savitha et al 2022;Wang et al 2019). Based on the empirical evidence, the following hypothesis was formulated.…”
Section: Trust and Fintech Usementioning
confidence: 99%